A compact rectangular patch ultra wideband antenna with WLAN band-rejection - Jalil Y.E.; Chakrabarty C.K.; Kasi B. (Institute of Electrical and Electronics Engineers Inc., 2023)
An ultra-wideband (UWB) antenna with filtering property is desirable to overcome the coexisting issue between UWB system and other established narrowband system. A compact UWB antenna integrated with a single band notched is presented in this paper. The proposed antenna is a rectangular patch antenna with a partial ground plane. A 50 ? microstrip line is used to feed the antenna. A band-stop function to eliminate the wireless local area network (WLAN) interfering signals is created by inserting an altered H-shaped slot on the proposed radiator. The proposed antenna shows a good impedance matching from 2.6 GHz to 10.8 GHz with a notched band from 5.15 GHz to 5.85 GHz. Furthermore, the presented structure has a compact size of 23.5 21 mm2 while exhibiting a good radiation pattern over the frequency range of interest. 2013 IEEE.